The Effect of Dynamic Electric Puzzle Science Tool-Assisted Inquiry Learning Model Towards Students’ Creative Thinking Skills - Eka Dewi; I Komang Werdhiana; Sahrul Saehana (Berkala Ilmiah Pendidikan Fisika, 2021)
The implementation of physics learning still does not involve students' thinking processes. It is very important to practice higher-order thinking skills, one of which is creative thinking. One of the mandated learning models in the 2013 Curriculum is inquiry. This study aimed to analyze the effect of dynamic electric puzzle science tool-assisted inquiry learning on students' creative thinking skills compared to conventional learning. This study used a quasi-experiment research type with a control group pretest-posttest design. This study was done in class XII. The sampling technique was purposive sampling, with XII IPA Al-Qalam as the experimented class and XII IPA Al-Furqan as the controlled class in the academic year of 2020/2021. Data collection was done by creative thinking skills instrument test, which consisted of 5 essay questions. Data were analyzed by using SPSS 25.0 for windows on normality, homogeneity, and N-gain test. Learning outcomes data of both classes were normally distributed and homogenous. Based on the result, the average score of the pretest and posttest of the controlled class were 39.2 and 70.7, while the average scores of the pretest and posttest of the experimented class were 49.0 and 80.2. Data analysis was done by using t test, and it resulted that tcount was 2.439, while ttable was 2.009 or tcount > ttable  and the significance was (0.01) < 0.05 meant that there was a significant effect of the inquiry model towards students' creative thinking skills if compared to conventional learning. The improvement of creative thinking skills in experimented class gained <g> score of 0.64, whereas the controlled class gained <g> score of 0.51. Inquiry learning assisted by dynamic electric puzzle science tools can increase students' opportunities to engage in inquiry-based activities and develop students' analytical and creative thinking skills.